1998
DOI: 10.1074/jbc.273.40.25741
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Dependence of the Toxicity of Short Chain Sugars

Abstract: Erythrose inhibited the growth of a sodA sodB strain of Escherichia coli under aerobiosis; but did not inhibit anaerobic growth of the sodA sodB strain, or the aerobic growth of the superoxide dismutase (SOD)-competent parental strain. A SOD mimic protected the sodA sodB strain against the toxicity of erythrose as did the carbonyl-blocking reagents hydrazine and aminoguanidine. Three carbon sugars, such as glyceraldehyde and dihydroxy acetone, and the two carbon sugar glycolaldehyde, were similarly toxic in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 27 publications
1
35
0
1
Order By: Relevance
“…By acting as the initial buffer against oxidative stress the release of iron from the aconitase proteins represents a potential source of danger because the combination of H # O # and iron generates highly reactive hydroxyl radicals that cause a wide range of DNA lesions (Keyer & Imlay, 1996 ;Nunoshiba et al, 1999). Conversely, there is evidence indicating that growth in an iron-enriched medium can partially compensate for the lack of SodA activity in E. coli (Benov & Fridovich, 1998). Moreover, it has been suggested that the oxidation of the [4Fe-4S] clusters by superoxide and the subsequent reassembly of the damaged clusters facilitated by iron enrichment could spare other targets from superoxide attack and still maintain [4Fe-4S]-enzyme activities at levels that continue to support metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…By acting as the initial buffer against oxidative stress the release of iron from the aconitase proteins represents a potential source of danger because the combination of H # O # and iron generates highly reactive hydroxyl radicals that cause a wide range of DNA lesions (Keyer & Imlay, 1996 ;Nunoshiba et al, 1999). Conversely, there is evidence indicating that growth in an iron-enriched medium can partially compensate for the lack of SodA activity in E. coli (Benov & Fridovich, 1998). Moreover, it has been suggested that the oxidation of the [4Fe-4S] clusters by superoxide and the subsequent reassembly of the damaged clusters facilitated by iron enrichment could spare other targets from superoxide attack and still maintain [4Fe-4S]-enzyme activities at levels that continue to support metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover a dimerization reaction would proceed even less well when the concentration of the monomer was very low. We have noted a toxicity of short chain sugars and have related it to the reactivity of the exposed carbonyl group and to the formation of enediolate tautomers, which can oxidize to very toxic ␣-␤ diketones (32). Hence short chain sugars should be kept at vanishingly low concentrations to prevent this.…”
Section: Why Omentioning
confidence: 99%
“…sodCII expression was confirmed by measurement of SodC protein levels in strains in which the promoters of sodCI and sodCII are switched, indicating that regulation of sodC expression in response to oxygen occurs at the level of transcription (data not shown). Anaerobic repression has been reported for the E. coli sodC gene (6,53), in which the iron-sulfur cluster-containing protein FNR, an oxygen-sensitive transcriptional regulator, has been suggested to be the primary regulator of anaerobic sodC repression (6). Salmonella SodCI and SodCII accumulation were therefore measured in an fnr mutant background.…”
Section: Abundance Of Sodci and Sodcii In Vitro And Within Intracellumentioning
confidence: 99%